Tahapan Hubungan Romantis dalam Menggunakan Aplikasi Kencan Online Bumble pada Perempuan di Kota Denpasar - Nabila, Indah Nur; Joni, I Dewa Ayu Sugiarica; Pradipta, Ade Devia; Damasemil, Calvin (E-Jurnal Medium, 2024)
The stages of building relationship in the era of technological advances certainly changes gradually. Starting from face-to-face, today can be online and mediated by the dating application Bumble. This study describes the stages of a romantic relationship using the Bumble dating application for women in Denpasar City using a descriptive qualitative research method based on Mark Knapp's Relationship Development Stages and Social Penetration Theory. It found that there are four stages of romanticism. The initiating stage of word selection in the first message. At the experimenting stage, it was found that there was an activity of exchanging information by asking questions and carrying out stalking and screening activities to add information. In the intensifying stage, there is a discussion of personal information based on self-disclosure. Integrating stage, is the formation of commitment between the informant and his partner to establish a relationship as a boyfriend of a romantic partner. Keywords Bumble Online Dating App, Computer Mediated Communication , Mark Knapp's Stages of Relationship Development, Social Penetration Theory.